The Effect of Moderate Aerobic Exercise on Information Retention - Clarkson, Sam; Dobratz, Marie; Fochs, Katilyn; Franz, Nicole; Nytes, Cassandra (Journal of Advanced Student Sciences (JASS), 2015)
Regular physical activity is associated with many benefits including decreased stress, improved mood, and improved memory and learning. Studies in mice and rats have shown that exercise directly affects hippocampal activity resulting in improved memory. While previous studies provide substantive evidence for the benefits of regular physical activity, we examined whether short-term physical activity before learning yields similar positive effects on information recall. In testing human participants’ recall both in resting and active settings, we examined if a positive correlation between acute exercise and memory would be apparent. Conversely, we examined if testing after rest, or participants not elevating physiological variables, would yield poorer performance results. The study investigated three physiological variables—heart rate, respiratory rate, and respiratory airflow—and compared recall performance with the variables baseline and elevated values. The effects of exercise were not statistically correlated with increased performance in our memory test. We found slight evidence supporting our hypothesis, but our results were mostly inconclusive. With some modifications, further research can better explain the role of exercise on memory and other cognitive function in humans.
An article that appeared in JASS, issue 2015
Keywords: airflow; aerobic; cognitive recall; heart rate; exercise; memory; memory retention; respiratory rate; word recognition